Chest Pain in a Renal Transplant Recipient due to Concomitant Cytomegalovirus and Herpes Simplex Virus Esophagitis - Seok Hyung Kang; Myong Ki Baeg; Sun-Hye Ko; Hyunjung Hwang; Sang Yeop Yi; Sung Jin Moon; Jeongkeun Park (Yong Chan Lee, 2019)
Chest pain in kidney transplant patients is usually caused by cardiac or pulmonary problems. However, it may be rarely caused by opportunistic esophageal infections. A 66-year-old female kidney transplant recipient was admitted because of chest pain. She had been treated with high-dose steroid and immunosuppressants for acute T-cell-mediated rejection. Cardiologic and pulmonary evaluations had normal results. Endoscopic examination revealed three clear ulcerative lesions in the esophagus. Histological and immunohistochemical staining of the endoscopic biopsy specimens revealed coinfection of herpes simplex virus and cytomegalovirus. The patient was treated with intravenous ganciclovir for 2 weeks. Her symptoms completely resolved, and follow-up endoscopy revealed complete healing of the previous ulcers. Viral esophagitis should be considered in the differential diagnosis in kidney transplant recipients presenting with chest pain.